Empowering Schools to Maintain the Health of School Environments in Indonesia and Malaysia : colaborating community services - Sri Widiyati; Ari Setiawan; Suparmin Suparmin; Nurizah Binti Mohamed Darwis; Laxmi Laxmi; Zul Azmi; Puji Hastuti; Eka Setiawati; Siti Nurhayati; Syafriani Syafriani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The prevalence of anemia among adolescent girls in Southeast Asia is categorized as a serious situation with a figure of more than 40 percent. Adolescents, especially girls, are a group that is very vulnerable to anemia, caused by menstruation which causes significant iron loss. Adolescent girls who are healthy and free from anemia will grow into healthy mothers and give birth to healthy children, so this initiative supports the first 1000 days of life program. Adolescent girls are ten times more likely to suffer from anemia than adolescent boys, because they menstruate every month and are in a growth phase that requires more iron intake. Education on handling anemia among adolescent girls aims to provide understanding and knowledge about anemia and the consequences faced. The target of this activity is adolescent girls at SMA Negeri 5 Padang City. Education is carried out through direct counseling and class discussions. It is hoped that participants can better understand and realize the importance of preventing anemia among adolescent girls.